Biologi Nilaparvata lugens Stall (Homoptera: Delphacidae) pada Empat Varietas Tanaman Padi (Oryza sativa L.) - Yaherwandi Yaherwandi; Reflinaldon Reflinaldon; Ayu Rahmadani (Universitas Syiah Kuala, 2009)
Biological parameters of insect pests is very important in testing the resistance of rice plants against brown plant hopper. This research aims to study the amount and duration of stage egg, nymph, imago, and the life cycle of brown plant hopper on four varieties of rice. The methods used in research was Complete Random Design with four treatments (variety of IR 64, Batang Piaman, Cisokan, and IR 42) and eight replications. Research data were analyzed using variance analysis and continued with List Significant Different (LSD) at 5% level. The results of research showed that the number and duration of stage egg, nymph, imago, and cycle time of brown plant hopper in four rice varieties were different. Number of egg, nymph, and imago were lowest in 64 IR varieties, while the highest was IR 42 variety. Stage of eggs and nymphs were the shortest in IR 42 varieties, while the longest were IR variety 64. Imago stage was the shortest in IR 64 variety, while longest was the variety IR 42. The life cycle of brown plant hopper were shortest in IR 42 varieties, while longest was the variety IR 64. The results of this study can be concluded that the IR 64 varieties more resistant than the varieties IR 42, Cisokan, and Batang Piaman based on stage of egg, nymph, and imago.